Measurement of jumper`s body motion in ski jumping - Ohgi, Y.; Seo, K.; Hirai, N.; Murakami, M. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
The authors propose motion analysis of ski jumping by data logging method using inertia sensors. A tri-axial accelerometer and a single axial gyroscope were attached onto the jumper`s body. Simultaneously, high speed cameras were equipped for the image capturing in order to obtain the jumper`s motion from the take-off and the middle phase of the flight. The characteristics of the ski jumper during whole phases were identified by using the inertia sensors.